LITERATURE REVIEW: THE EFFECT OF INFLATION ON THE PROFITABILITY OF MSMEs IN WEST JAVA, INDONESIA (2019-2024) - Padmiswari, Ni Luh Putu Dian; Savitri, Ni Luh Asri (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study provides a comprehensive analysis of the sectoral impact of inflation on Micro, Small, and Medium Enterprise (MSME) profitability in West Java, Indonesia, during the 2019-2024 period. As MSMEs constitute the backbone of West Java's economy, contributing significantly to regional GDP and employment, understanding their vulnerability to macroeconomic fluctuations is crucial. This research addresses a critical gap in the existing literature by moving beyond generalized approaches to examine the nuanced, sector-specific effects of inflationary pressures. Employing a systematic narrative literature review methodology, this study synthesizes empirical evidence from diverse secondary sources, including statistical reports from BPS and Bank Indonesia, as well as scholarly publications. The analysis reveals pronounced sectoral heterogeneity: food-based MSMEs experience substantial profit margin compression due to input price volatility, while creative industry enterprises demonstrate remarkable resilience through export orientation and product diversification strategies. Service-oriented MSMEs face moderate challenges associated with diminished local purchasing power. These findings underscore the necessity for differentiated policy approaches that acknowledge sectoral characteristics. The study concludes that effective economic planning requires tailored interventions rather than one-sizefits-all solutions, recommending targeted support mechanisms such as input subsidies for agricultural MSMEs and export facilitation programs for creative industries to enhance sector- specific resilience against inflationary challenges.